Value Chain Analysis Of Palm Oil In Indonesia (Case Study In East Borneo Province) - Antonio Sipayung (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
The supply of palm oil in East Kalimantan Province does not only come from state-owned and private plantations but also smallholders. The palm oil value chain analysis was conducted in three districts in several palm oil companies and their suppliers. CPO and PKO production data are taken through secondary data and have been processed. The company has a core business in the field of processing crude palm oil (CPO) derived from fresh fruit bunches (FFB) owned by its plantations and from farmer groups around the oil palm plantation and oil palm processing (PKO) areas. The capacity of crude oil processing plants (CPO) varies from the lowest, 30 tons FFB/hour to 90 tons FFB/hour. The purpose of this study was to analyze the CPO supply value chain of several companies in East Kalimantan Province. Observational data are taken directly in the field and secondary data. The CPO generated by Oil Palm Mill is used for two of its activities: vegetable oil, and B. non-vegetable oil. Vegetable oil is used for cooking oil and margarine. However, non-vegetable oils are used in biodiesel (for renewable energy) and soaps, and shampoos. Kernel aims for his two activities: The use of cosmetics, perfumes, or drugs.